2012
DOI: 10.1021/ja310003v
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium Phosphasalen Initiators for rac-Lactide Polymerization: Excellent Rates and High Iso-Selectivities

Abstract: Highly active yttrium phosphasalen initiators for the stereocontrolled ring-opening polymerization of rac-lactide are reported. The initiators are coordinated by a new class of ancillary ligand: an iminophosphorane derivative of the popular "salen" ligand, termed "phosphasalen". Changing the phosphasalen structure enables access to high iso-selectivities (P(i) = 0.84) or hetero-selectivities (P(s) = 0.87). The initiators also show very high rates, excellent polymerization control, and tolerance to low loadings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
143
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(149 citation statements)
references
References 48 publications
5
143
1
Order By: Relevance
“…17,[33][34][35][36] Schiff base metal complexes have found numerous uses in coordination chemistry and catalysis, [37][38][39][40][41][42] alkoxide yttrium complexes supported by such ligands being intensely researched as initiators for the ring-opening polymerization of cyclic esters. 17,[35][36][43][44][45][46][47][48][49][50] On the other hand, reports of structurally characterized alkyl or aryl rare earth complexes bearing an imine functionality in the backbone are rare, [51][52] the majority being represented by phosphinimine ligands. [53][54][55][56][57][58][59][60] In our lab, the synthesis of an electrophilic metal alkyl complex supported by a Schiff base ferrocene ligand would continually fail.…”
Section: Introductionmentioning
confidence: 99%
“…17,[33][34][35][36] Schiff base metal complexes have found numerous uses in coordination chemistry and catalysis, [37][38][39][40][41][42] alkoxide yttrium complexes supported by such ligands being intensely researched as initiators for the ring-opening polymerization of cyclic esters. 17,[35][36][43][44][45][46][47][48][49][50] On the other hand, reports of structurally characterized alkyl or aryl rare earth complexes bearing an imine functionality in the backbone are rare, [51][52] the majority being represented by phosphinimine ligands. [53][54][55][56][57][58][59][60] In our lab, the synthesis of an electrophilic metal alkyl complex supported by a Schiff base ferrocene ligand would continually fail.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that these ligands are more flexible and electron-donating than their carbon analogues [12] and that they provide efficient and selective initiators for rac-lactide polymerization. [13] In the present work, we wish to report the synthesis and characterization of a Ni II phosphasalen complex and its one-electron oxidation which leads to a temperaturepersistent high-valent tetracoordinated Ni III complex. With the objective of studying the oxidation of a [Ni-(Psalen)] complex, we chose a ligand featuring substituents on the ortho and para positions of the phenoxide rings to increase its stability, and preferred tert-butyl groups for solubility reasons.…”
mentioning
confidence: 99%
“…Very recently, Auffrant and Williams reported that yttrium phosphasalen complex (33) shows high isoselectivity as well as high activity for the polymerization of rac-lactide. The combination of such very high rates, excellent polymerization control, tolerance to low loadings, and high isoselectivity is very rare and noteworthy (106). Mg complexes with diamide ligand such as 34 promote isotactic polymerization of rac-lactide to afford stereoblock copolymer, although P m is not clear (107).…”
Section: Polymerization Of Lactidesmentioning
confidence: 99%